Barriers to COVID-19 Workplace Safety among Indonesian Office Workers: A Qualitative Study - Handayani, Sri; Nuraini, Syarifah; Fiitrianti, Yunita; Agustiya, Rozana Ika; Kurniawan, Aan; Propiana, Jane Kartika (The Indonesian Journal of Occupational Safety and Health, 2025)
Introduction: Since the first case of COVID-19 was detected in Indonesia, the government has implemented Large-Scale Social Restrictions to control the spread of the disease. However, these restrictions have had a negative impact on the economy. To address this, the government has introduced a new normal policy to restore activities while managing the risk of transmission. The government has adopted WHO guidelines through Minister of Health Decree No. 238 of 2020 to ensure COVID-19 workplace safety. This article aims to explore the barriers to COVID-19 workplace safety among Indonesian office workers. Methods: This qualitative research was conducted in DKI Jakarta and Surabaya from September to October 2020. In-depth interviews and observations were conducted with 22 informants selected purposefully. Thematic analysis was used, drawing on the Social-ecological Model (SEM) theory. Results: At the intrapersonal level, fear and perception barriers impact preventive actions against COVID-19. At the interpersonal level, peer influence and perceptions of the work environment affect adherence to office policies. At the organizational level, employee behavior is influenced by socializing, rules, and workplace amenities. Lastly, public policy enforcement is vital at the macro level to reduce risky behaviors among office workers. Conclusion: Implementing comprehensive protocols across different levels is crucial to creating COVID-19 workplace safety. This requires increased public awareness and consistent enforcement, including strengthening organizational policies.